PENGARUH BAURAN PEMASARAN TERHADAP MINAT BERKUNJUNG KEMBALI KE PD. TAMAN SATWA KEBUN BINATANG SURABAYA - Muhammad Ali Rafif, Widyatmoko; Sonja, Andarini (Jurnal Bisnis Indonesia, 2021)
This study aims to determine the effect of the marketing mix on the interest of visiting agai toPD Taman Satwa Zoo Surabaya. This study uses independent variables (X) namely Product(X1), Price (X2), Promotion (X3), Place (X4), Person (X5), Process (X6) and Physical Proof(X7), and dependent variable (Y ) Visiting Interest again. The population is all visitors whomake a Visiting Interest again to the Surabaya Zoo. Purposive sampling technique with a totalsample of 100 respondents. The data analysis method used is multiple linear regressionanalysis. The results obtained from this study indicate simultaneously the product variables,nutrients, promotions, places, people, physical evidence, and the process of influencing thevariable of Visiting Interest again. Then partially only product, price, place, people, andprocess variables that influence Visiting Interest again. While the promotion variable andphysical evidence do not affect for Visiting Interest again.Keywords: Marketing Mix, Visiting Interest again  DOI : https://doi.org/10.33005/jbi.v12i1.2607